Entrepreneur Willingness in Case of Students of University of Debrecen - Kun, Gergő (International Journal of Engineering and Management Sciences, 2018)
This article is about the entrepeneur willingness in case of the students of University of Debrecen. There was 500 participants in the paper and online based survey who could tell their opinion about entrepreneurship in Hungary, what difficulties are they seeing and which part of the economy is where they see opportunity to start their own business. The aim of this article is to get to know how many of them and with what rate would like to start their own business, while it is examined they are from which faculty of the University, what is their family background and these facts how effects on the individual if his or her family owns some kind of business.